Gambaran pengetahuan dan sikap GMIM Viadolorosa Kairagi II Manado mengenai penanganan korban kekerasan terhadap perempuan - Rosaline, Sheila; Ratag, Gustaaf A. E.; Sapulete, Margareth R. (UNIVERSITAS SAM RATULANGI, 2016)
Purpose: To describe the knowledge and attitudes of pastor GMIM Via Dolorosa in terms of addressing violence against women. Methods: The study was descriptive qualitative grounded theory approach, technique-depth interviews and focus group discussion (FGD) to four pastors GMIM. Results and Conclusion: All four pastors have a fairly good knowledge about the handling of victims of violence against women, although not too deep. Pastors overall have positive attitude in the handling of victims of violence against women. Keywords: knowledge, attitude, pastor, handling victims, violence against women